Chemical Modification of Teff Straw Biomass for Adsorptive Removal of Cr (VI) from Aqueous Solution: Characterization, Optimization, Kinetics, and Thermodynamic Aspects - Ashagrie Liyew Ayele; Belachew Zegale Tizazu; Abrham Bayeh Wassie (Adsorption Science & Technology)
Teff straw, a by-product of Teff, mainly available in Ethiopia, has not been studied much for biosorbent production. The present study has investigated the effects of modification and optimization of process parameters (viz., concentration of modifying agent (H3PO4 and KOH), modifying temperature, and modifying time) on the Cr (VI) removal efficiency of using chemically activated Teff straw biosorbent by RSM followed by BBD. The maximum Cr (VI) removal was obtained using an H3PO4-modified Teff straw biosorbent of 92.5% with 2 M concentration of the modifying agent, 110°C, and 4 h. Similarly, maximum Cr (VI) removal using KOH-modified Teff straw biosorbent of 95.2% was obtained with 1.5 M activating agent concentration, 105°C activation temperature, and 3.5 h activation time. In addition, the effects of adsorption parameters (viz., biosorbent dosage, temperature, initial concentration of Cr (VI), and contact time) were investigated. The maximum removal efficiency was attained at 2 g of biosorbent dosage, 4 h contact, 75 mg/L of initial Cr (VI) concentration, and 25°C sorption temperature. In addition, isotherm, kinetic, and thermodynamic studies for Cr (VI) biosorption were studied. The experimental adsorption data were well fitted with the Langmuir isotherm and pseudo-second-order kinetic model with higher correlation coefficient in both untreated and chemically modified Teff straw biosorbent. The investigated thermodynamic parameters (ΔHo, ΔSo, and ΔGo) confirmed that Cr (VI) metal ions’ adsorption process onto Teff straw biosorbent was spontaneous and endothermic.